Uveitic glaucoma and Rosai-Dorfman disease (sinus histiocytosis). - Maclaren, R; Hundal, K; Trittibach, P; Bloom, P (2006)
PURPOSE: To report a novel association of uveitic glaucoma with Rosai-Dorfman disease. METHODS: Case report. RESULTS: A 67-year-old Caucasian woman presented with a chronic bilateral granulomatous uveitis which did not respond to conventional topical steroid therapy. She also had raised intraocular pressures, glaucomatous optic disc changes and diffuse nodular fibrous skin lesions. Subsequent skin biopsy immuno-cytochemistry showed S-100 staining, consistent with Rosai-Dorfman disease. The uveitis and glaucoma were highly resistant to standard medical treatments, but completely resolved together with the systemic features of the disease after six months. CONCLUSIONS: Rosai-Dorfman disease has not previously been reported to cause uveitic glaucoma and should be considered in non-responsive cases presenting with a rash. The disease is entirely self-limiting and early diagnosis may therefore avoid unnecessary trabeculectomy and/or systemic immune suppression.